Hubungan Perkembangan Balita Dengan Perilaku Dan Emosional Di Wilayah Puskesmas Kaliwates Jember - Sari, Asri Iman; Zannah, Ai Nur; Yuningsih, Yuningsih (Puslitbang Sinergis Asa Professional, 2024)
The Indonesian Ministry of Health stated that around 400,000 toddlers in Indonesia suffer from developmental disorders. Based on Riskesdas 2013 data, the prevalence of stunting is 37.2%. Development can be assessed using motor skills, social and emotional skills, language skills, and cognitive skills. Children have the right to receive attention in the process of growth and development so as to achieve a good quality of life, to achieve a good future for the nation. The aim of this study was to analyze the relationship between the developmental status of stunting toddlers and their behavior and emotions at the Kaliwates Health Center, Jember district. The population of this study were 70 toddlers who came to posyandu in the Kaliwates Health Center, Jember Regency, and the sample was taken by total sampling. Measurement of growth and development of toddlers using the book Stimulation, Detection and Early Intervention of Growth and Development (SDIDTK). The research showed that 39 toddlers developed according to their age and 31 toddlers experienced developmental delays and required follow-up. Behavioral and emotional toddlers showed that 3 toddlers did not experience behavioral and emotional problems, while 67 toddlers experienced problems. The statistical test used the contingency coefficient and obtained a p-value of 0.047 with a significant level of 5%. It can be concluded that there is a relationship between the development of stunting toddlers with their behavior and emotions.